Pengaruh Value Based Management Pada Nilai Ekuitas Perusahaan Dengan Corporate Social Responsibility Sebagai Variabel Pemoderasi - Nina Fitri (Journal Economy and Currency Study (JECS), 2021)
The purpose of this research is to examine that the disclosure of Corporate Social Responsibility moderate the relationship of Value-Based Management with the corporate equity. This research was conducted at the Indonesian Stock Exchange in the year 2019 to 2020. Purposive sampling method was used to determine samples and 103 observations were obtained. The statistical analysis which was done included the classic assumption test and goodness of fit test. Testing the influence of moderating variables in this research hypothesis was conducted using Moderated Regression Analysis (MRA) which is a special application of multiple linear regressions. Based on the research results and their discussions, it can be concluded that the disclosure of Corporate Social Responsibility is not proven significantly as a moderating variable of the relationship between the Value-Based Management with the corporate equity. It is indicated that way because investors do not need to look at the disclosure of Corporate Social Responsibility anymore which has no longer been a voluntary but a mandatory. Using Value-based Management as an indicator which is measured by the Economic Value Added, the investor does not consider the corporate social responsibility in making investment decisions. This is consistent with the concept of Value-based Management that investors tend to have a main purpose to obtain maximum returns from investment with the view that the economic value of a commercial enterprise is legitimated only by the benefits gained.